Survival analysis and prognostic factors for peri-ocular malignancies in Malaysia - Sivaratnam, Dhashani; Othman, Radzlian; Devaraj, Navin Kumar; Teck, Yap Ming; Fung, Vincent Ng Teng; Chen, Ew Shao; Rozi, Ramizah Md; Baharudin, Nur Najlaa; Kanasan, Kirbashini; Khan, Abdul Hanif Khan Yusof; Ramachandran, Vasudevan; Ching, Siew Moi (Universiti Putra Malaysia Press, 2024)
Introduction: This study aims to determine the prognostic factors and survival outcomes of patients that underwent this surgery. Method: A retrospective review of 43 patients who underwent exenteration for periocular malignancies over a 14-year period was carried out. Patient demographics, tumour histology, treatment details, surgical margins’ status and post-operative survival were recorded. The survival outcome examined was the overall survival (OS) rate. Cox regression and Kaplan-Meier analysis were used to evaluate post-exenteration survival. Results: In total, 20 females and 23 males with a median age of 62 ± 17.3 years were identified. The most common indication for exenteration was basal cell carcinoma (20.9), followed by squamous cell carcinoma (18.6), adenocystic carcinoma (14), malignant melanoma (14) and sebaceous gland carcinoma (11.6). The independent predictors for worse OS on multivariate analysis were Chinese ethnicity (adjusted hazard ratio aHR 4.95, p =0.017), sebaceous gland carcinoma (aHR 57.61 p=0.006), adenocystic carcinoma (aHR 45.87, p=0.008), clear surgical margins (aHR 5.41, p=0.025), receiving only chemotherapy (aHR 169.13, p=0.004), and receiving both adjuvant chemotherapy and radiotherapy (aHR 41.51, p=0.010). Conclusion: We recommend targeted public health initiatives for Chinese patients due to their increased mortality risk from peri-ocular malignancies. In addition, we advise comprehensive adjuvant therapy for all patients regardless of whether a clear surgical margin is achieved. Basal cell carcinoma and adenocystic carcinoma may also benefit from genetic research. We advocate more training for ophthalmologists to identify periocular malignancies earlier for better treatment options and increased chances of survival.